How does China’s green factory policy affect substantive green innovation? - Xiangshu Dong; Yongjiao Du; Xiang Xiao (PLoS ONE, 2025)
Green factory evaluation (GFE) is a green industry policy in China with the goal of accelerating green manufacturing. How does GFE influence corporate substantive green innovation (SUGI)? Existing research has yet to provide definitive results. Based on GFE policy, this paper utilizes the data of China’s A-share listed manufacturing firms spanning 2012–2021 by the time-varying difference-in-differences model to investigate the impact of GFE on SUGI. The results indicate that GFE can significantly improve corporate SUGI. The mechanism results suggest that GFE promotes corporate SUGI by limiting greenwashing and enhancing industry-university-research cooperation. Additionally, we find the impact of GFE has greatly boosted corporate SUGI in industries characterized by high energy consumption and pollution levels, suggesting a potential disruption of technological path dependencies within these sectors. Moreover, firms with extensive external information disclosure exhibit stronger enhancements in SUGI under GFE. The conclusions confirm the effect and internal logic of GFE’s influence on corporate SUGI and provide a valuable advice for relevant policies aimed at improving green development.